2015
DOI: 10.1007/s40429-015-0077-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship Between Amphetamines and Psychosis

Abstract: Use of amphetamine and methamphetamine (hereafter amphetamines) can cause acute psychotic symptoms and may also contribute to persistent psychotic conditions such as schizophrenia. Still, much remains uncertain about the mechanisms and nature of this relationship. In this paper, we review certain aspects of this relationship, with particular emphasis on papers published during the past 3 years. A review of the literature reveals that, in addition to the established knowledge that amphetamines can cause acute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 77 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…In addition, some studies have not sufficiently accounted for or excluded individuals with primary psychotic disorders. Although there have been three previous narrative reviews focussing on factors associated with MA psychosis (Bramness et al, 2012; Glasner-Edwards and Mooney, 2014; Rognli and Bramness, 2015), these have not utilised systematic methodology and have not attempted to evaluate the quality of studies or potential sources of bias.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have not sufficiently accounted for or excluded individuals with primary psychotic disorders. Although there have been three previous narrative reviews focussing on factors associated with MA psychosis (Bramness et al, 2012; Glasner-Edwards and Mooney, 2014; Rognli and Bramness, 2015), these have not utilised systematic methodology and have not attempted to evaluate the quality of studies or potential sources of bias.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Norwegian study found no association between the severity of psychotic symptoms and quantitative measures of blood amphetamine concentration ( 16 ). In addition, there have been three narrative reviews focusing on risk factors associated with MIP ( 4 , 17 , 18 ), showed that it was complicated to determine causality for the MIP, and difficult to make clear about the risk factors of psychotic disorders among MA users.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, this information could be of clinical importance as it helps to understand variations in both behavioral responses to low doses of AMPH (≤ 0.25 mg/kg/day) and the incidence of behavioral sensitization after intermittent usage of low doses in humans [39,42,43].…”
Section: Discussionmentioning
confidence: 99%